Consumers' willingness to pay for second-generation ethanol in Brazil. (February 2022) - Garcia, Teresa Cristina; Durand-Morat, Alvaro; Yang, Wei; Popp, Michael; Schreckhise, William
Abstract: Although Brazil has great potential to commercially produce second-generation ethanol (E2G), almost all ethanol currently produced in Brazil is first-generation ethanol (E1G). Considering that Brazil does not have a federal mandate requiring increased deployment of E2G to meet their biofuel blending requirement, the extent to which a market for E2G emerges will depend in part on the potential premium consumers are willing to pay for E2G. This work summarizes a consumer survey about their willingness to pay (WTP) for E2G. The survey was conducted in 24 Brazilian states to assess how WTP for E2G is affected by respondents' driving habits, knowledge about biofuels, acceptance of relevant biofuel policies, and demographic characteristics. Using dichotomous-choice contingent valuation, we found that, on average, Brazilian consumers are willing to pay an 8.5 percent premium for gasoline blended with E2G. We estimate that an 8.5 percent price premium is enough to use as much as 62.5 percent of E2G in the currently mandated E27 blended fuel (E27) without the need of government support/subsidies. Results also suggested that consumers more informed about biofuels and with higher income are more likely to pay a premium for E2G. Informing consumers about E2G thus would enhance likelihood of adoption. Highlights: Willingness to pay (WTP) for second-generation ethanol (E2G) in Brazil was assessed. Brazilian consumers are WTP an average 8.5% premium (R0.35 more per liter) for E2G. Knowledge about biofuels and income level have a significant impact on WTP. The premium is large enough to support E2G with little government support in Brazil.